Bibliometric analysis of watermelon marketing study trends in Indonesia - Napitupulu, Tia Sofiani; Sumarlina, Sumarlina; Marseva, Amalia Dwi; Husnudin, Uni Baroroh (Journal of Agricultural Socio-Economics (JASE), 2024)
Watermelon marketing studies play an important role in creating a more efficient and profitable marketing system in an effort to support the development of watermelon farming in Indonesia. Although watermelon marketing studies in Indonesia have covered various aspects such as channels, margins, strategies, and marketing efficiency, there are still limitations in the distribution of research locations and the lack of completeness of the dynamics of subtopic trends longitudinally. The bibliometric analysis method can be used to trace research trends related to watermelon marketing which consists of three stages, namely data collection, data analysis, and data visualization. The selected data is analyzed by comparing the attributes they have. Based on the selection, representative publications only come from 2011 to 2024. Studies related to watermelon marketing in Indonesia show a very fluctuating trend in terms of years. Research topics related to watermelon marketing in Indonesia generally focus on topics related to marketing analysis and specifically focus on the study of marketing channels, marketing margins, marketing strategies, and marketing efficiency in watermelon farming. The locations of research related to watermelon marketing in Indonesia are mostly found on the islands of Java (37%) and Sumatra (33%). However, research related to watermelon marketing is also found in various other regions in Indonesia, namely the islands of Kalimantan, Sulawesi, Maluku, and Madura. In addition, the results of this study also show a trend of shifting subtopics of research related to watermelon marketing.